Antibacterial Activity of Some Essential Oils/Herbal Extracts Against Bacteria Isolated from Ball Pythons (Python regius) with Respiratory Infections - Corina Pascu; Viorel Herman; Luminita Costinar; Corina Badea; Valentin Gros; Georgeta Stefan (Antibiotics, 2025)
Background: Respiratory diseases are among the main causes of morbidity and mortality in captive reptiles. In Romania, pneumonia is a frequently observed illness affecting pet reptiles. Key factors contributing to the high incidence of pneumonia include inadequate animal husbandry, poor nutrition, and insufficient hygiene practices. Bacteria may act as primary pathogens or as facilitators of disease severity. Methods: This study investigates bacterial strains from multiple genera and species (Chryseobacterium (C.) indologenes, Staphylococcus (S.) epidermidis, Escherichia (E.) coli, and Pseudomonas (P.) aeruginoasa) from six ball pythons regarding their antibiotic susceptibility and the effect of essential oils. Bacteria were isolated from the lower respiratory tract, displaying clinical signs of pneumonia. All isolates were tested with essential oils (lemongrass, oregano, rosemary, and sage) and a grapefruit seed extract (GSE) at different dilutions. Results: The incidence of Chryseobacterium indologenes was highest (3 isolates/12 samples, 25%), followed by E. coli and Staphylococcus epidermidis (2/12 each, 16.6%), and Pseudomonas aeruginoasa (1/12, 8.3%). Resistance profiling to different antibiotic classes revealed that all isolates (eight) were resistant to multiple antibiotics tested by us. All isolates were resistant to β-lactams and fluoroquinolones. One strain of E. coli exhibited intermediate resistance to quinolone and penicillin. All strains were categorized as multidrug-resistant. GSE showed antibacterial activity against all isolates. Conclusions: Wanting to deepen our understanding of the microorganisms that can infect ball pythons and recognizing that all isolated bacteria have zoonotic potential, this paper highlights some common issues faced by exotic animal owners and suggests that treatments should also include the use of essential oils.